The humanistic tradition - Fiero, Gloria K (Boston, MA, 2006)
The Humanistic Tradition features a flexible, topical approach that helps students understand humankind's creative legacy as a continuum rather than as a series of isolated events. This widely acclaimed interdisciplinary survey offers a global perspective, countless illustrations, and more than 150 literary sources. Available in multiple formats, The Humanistic Tradition explores the political, economic, and social contexts of human culture, providing a global and multicultural perspective which helps students better understand the relationship between the West and other world cultures
Keywords: Civilization, Western,Humanism,Văn minh, phương tây,Chủ nghĩa nhân đạo; History,History,Lịch sử,Lịch sử